PERAN PETANI TEMBAKAU DALAM AKTIVITAS SUBAK (KASUS DI SUBAKGEDE SUKAWATI, DI KECAMATAN SUKAWATI, KABUPATEN GIANYAR) - Wijayanti, Putu Udayani (dwijenAGRO, 2011)
â??The subakâ? which organized the distribution of water at rice fields is one of the inheritance of Bali culture. Its existence is developed because Bali society tends to increase the rice plantation. Threaten to unspoiled of â??the subakâ? is derive from various changes of social life of Bali society.The objectives of this experiment were: to observe various changes of â??the subakâ? activities which is occur after plantations of tobacco. Farmers were observed with qualitative and descriptive analyzed. Data were analyzed with method of Chi Square.Â Keywords: subak, rice fields